A Single-Stage Isolated Battery Charger Using Nonbridged Positive Cuk Converter Configuration - Tanmay Shukla; N. P. Patidar; Apsara Adhikari (IET Electrical Systems in Transportation)
This article presents a nonbridged isolated positive Cuk (NB-IPCuk) converter-based single-stage battery charging system (SSBCS). The architecture of the suggested charger ensures the intrinsic advantage of power quality improvement in discontinuous current conduction (DCC) mode at the supply mains. The suggested NB-IPCuk converter scheme has fewer components than other bridgeless/nonbridged Cuk converter schemes. This is because the NB-IPCuk converter is a partial integration of two Cuk converters. The usage of the Cuk converter garnishes the system with input and output inductances, which lessens supply current harmonic distortion and, thus supply terminal low pass filter requirement is eradicated. The advantages of the NB-IPCuk converter are the eradication of one inductor and multiple diodes (two back-feeding diodes), which are generally used in NB converter configurations. In place of two separate inductors, the NB-IPCuk converter uses a single secondary side output inductor. The usage of BL configuration of NB-IPCuk converter eradicates the bridge rectifier (BR) stage, and thus, the BR-associated losses also got eradicated. The NB-IPCuk converter also garnishes the system with electrical isolation which adds to the safety standards of the system. DCC mode operation of the NB-IPCuk converter is used in the present work. DCC mode requires lesser sensors in comparison to continuous current conduction mode. The abovementioned benefits of the NB-IPCuk converter make the SSBCS system cheaper, compact, and more efficient. The detailed stability analysis (Bode diagram and pole-zero map) and mathematics for the NB-IPCuk converter are also included in the paper. The prototype and MATLAB/Simulink model of NB-IPCuk converter-based SSBCS system with DCC mode control has been built, and results of both prototype and MATLAB/Simulink are deployed to verify SSBCS system’s performance during dynamic and steady-state conditions.